Assessment of crude glycerol for Enhanced Biological Phosphorus Removal: Stability and role of long chain fatty acids. (December 2015) - Tayà, Carlota; Guerrero, Javier; Suárez-Ojeda, María Eugenia; Guisasola, Albert; Baeza, Juan Antonio
Graphical abstract: Highlights: Crude glycerol with low content of LCFA is a suitable carbon source for EBPR. EBPR activity with LCFA as sole carbon source is demonstrated for the first time. High LCFA content leads to its adsorption on the biomass surface and EBPR failure. Cell hydrophobicity increases with long-term utilization of LCFA. Abstract: Enhanced Biological Phosphorus Removal (EBPR) of urban wastewaters is usually limited by the available carbon source required by Polyphosphate Accumulating Organisms (PAO). External carbon sources as volatile fatty acids (VFA) or other pure organic compounds have been tested at lab scale demonstrating its ability to enhance PAO activity, but the application of this strategy at full-scale WWTPs is not cost-effective. The utilization of industrial by-products with some of these organic compounds provides lower cost, but it has the possible drawback of having inhibitory or toxic compounds to PAO. This study is focused on the utilization of crude glycerol, the industrial by-product generated in the biodiesel production, as a possible carbon source to enhance EBPR in carbon-limited urban wastewaters. Crude glycerol has non-negligible content of other organic compounds as methanol, salts, VFA and long chain fatty acids (LCFA). VFA and methanol have been demonstrated to enhance PAO activity, but there is no previous study about the effect of LCFA on PAO. This work presents the operation of an EBPR SBR system using crude glycerol as sole carbon source, studying also its long-term stability. The effect of LCFA is evaluated at short and long-term operation, demonstrating for the first time EBPR activity with LCFA as sole carbon source and its long-term failure due to the increased hydrophobicity of the sludge.